ChemInform Abstract: Two New Acidic Diterpenoids from the Heartwood of Pinus massoniana Lamb. Issue 9 (March 2015) - Abd. Mohamed, H.; Hsieh, Chin‐Lin; Hsu, Chin; Kuo, Ching‐Chuan; Chang, Hsuan‐Shuo; Lee, Ching‐Kuo; Lee, Tzon‐Huei; Wu, Jin‐Bin; Chang, Chi‐I; Kuo, Yueh‐Hsiung
Abstract isolation and structure determination of a new abietane diterpene, named abietopinoic acid (I), and a new podocarpane diterpene, podopinoic acid (II)